Perancangan Sistem Kontrol Hybrid Pada Segway Beroda Dua Berbasis Matlab/Simulink - Tantra Nagendra, I Made Mahatma; Widhiada, I Wayan; Adi Atmika, Ketut (Teknik Desain Mekanika, 2021)
Abstractt Segway is simple transport equipment with electricity power source that is more environmentally friendly and more power efficient. Segway is designed in such a way as to facilitate mobility in short distance transportation both outdoors and indoors. So that the prototype designed in this study, using inverted pendulum theory and control system modeling. This research is only limited to balancing the Segway prototype statically with an external force in the form of a reference angle of 15o and -15o using a hybrid control system. Where the hybrid control system is a combination of PID control system and Fuzzy Logic which is designed using the matlab / Simulink software. In purpose of getting overshoot, error under 5% and minimal settling time. Keywords: Segway, Balancing robot, Control, Matlab